Exploring algal technologies for a circular bio-based economy in rural sector. (20th June 2022) - Vishwakarma, Rashi; Dhaka, Vidushi; Ariyadasa, Thilini U.; Malik, Anushree
Abstract: A circular bio-based economy is based on the recycling of nutrients, reduction and utilization of wastes as a feedstock for processes that can generate various bioproducts. This review discusses the advantages and constraints in integrating algal technologies to establish an environmentally preferable circular biobased rural economy with a great potential to recover resources, diversify livelihood options and enhance socioeconomic conditions. Scattered work is available in integrating algal technologies with aquaculture, poultry, livestock and agriculture. An overview of these studies depicts that effluents from aquaculture and agricultural run-off can be directly utilized for algal cultivation while high strength poultry litter and livestock waste are generally anaerobically digested followed by algae cultivation on the digestate. Alternatively, studies have also attempted direct utilization of poultry/livestock effluents after suitable pretreatments like filtration, dilution etc. In most of the studies with right selection of the algal-bacterial consortia and cultivation system design, significant biomass yields (greater than those on expensive cultivation media) have been obtained. Apart from conventional challenges such as large footprint, energy intensive harvesting and processing, additional concerns for safety of the wastewater grown biomass needs to be overcome through thorough toxicity evaluations of the field samples. Standalone studies on use of algal biomass as feed supplement in these sectors are available that demonstrate several benefits such as improved quality and quantity of products in poultry and aquaculture. Significant reductions in production costs are projected by incorporating locally cultivated algal biomass as feed supplement that boosts immunity, and this may reduce expenditures on antibiotics and other pharmaceuticals as well. This aspect points towards strong commercialization potential. However, very few long-term studies are available to establish the feasibility of integrating algal biomass produced on waste streams from aquaculture, poultry, livestock, agriculture as feed supplement in the same or allied sector. Such efforts are important for closing the loops and fostering bio-based circular economy. On the other hand, bioenergy and land applications of wastewater grown algal biomass have attended greater maturity. Scale-ups under outdoor conditions, though limited, have also been reported but complete utilization of harvested biomass and/or downstream processing for obtaining valuable bioproducts remains elusive and is often represented as projected values. Hence, more pilot demonstrations and Life Cycle Analysis (LCA) of the complete process based on the actual data from field scale integrated systems is needed to facilitate actual implementations. Moreover, a framework for involving local village communities in such demonstration projects is vital to access the social acceptance of such interventions. Graphical abstract: Image 1 Highlights: Pros & cons of algae mediated resource recovery from rural sector wastes presented. High strength poultry/livestock waste challenging but high biomass potential. Pilot scale studies on waste treatment coupled bioenergy/land applications of biomass available. Long term field demos and product safety evaluations for feed/high-end use needed. Policy interventions, community skill development & industrial linkages lacking.